Successful Treatment of Unresectable Advanced Melanoma by Administration of Nivolumab With Ipilimumab Before Primary Tumor Resection - Fujimura, Taku; Kambayashi, Yumi; Sato, Yota; Tanita, Kayo; Amagai, Ryo; Hashimoto, Akira; Hidaka, Takanori; Aiba, Setsuya (Frontiers in Medicine, 2019)
Ipilimumab, in combination with nivolumab, is one of the promising drugs that enhance the anti-tumor immune response of patients with advanced melanoma. Since the co-administration of nivolumab with ipilimumab in the neoadjuvant setting expands melanoma-reactive T cells at the primary site of melanoma and has a high rate of histological complete response, the pre-surgical administration of this combination could be the optimal therapy for unresectable advanced melanoma. In this report, a case of unresectable advanced melanoma treated successfully with administration of nivolumab with ipilimumab before primary tumor resection is presented. In addition, CD8+ T cells increased among the tumor-infiltrating lymphocytes that were surrounding melanoma cells and caspase 3+ cells. The present case suggests that pre-surgical administration of nivolumab with ipilimumab could be the optimal therapy for the treatment of unresectable advanced melanoma.